‘I would say the mark itself, it doesn't tell the whole story’: the student view of what success means - Gwenda Mynott (Journal of Learning Development in Higher Education)
This paper presents and discusses the findings of a research study that aimed to investigate how undergraduate Business students measure the success of their own learning. The setting was a post-1992 university in the North-West of England. Higher education institutions and government policy can appear fixated on student success as a quantifiable outcome of an undergraduate degree course; it is something that can be measured via the grading system. As such, the meaning of student success can appear to be straightforward; however, this paper sets out to question this assumption. The findings of the study show that how students thought lecturers measured success was markedly different from how they talked about measuring their own success. They viewed lecturers as being focused on things that could be measured, such as grades. How the participants talked about their own success was far more nuanced and it focused on emotion in addition to grades. For the participants, success meant proving something to themselves and the enjoyment of having learnt something new. Another notable finding was that the participants wanted to feel they had earned their success through challenge and hard work. The contribution this study makes to knowledge is to add to a small and important body of work on how undergraduate students view success. It challenges the normalised identity of an undergraduate Business student as being grade-focused and, in doing so, argues that an understanding of the enjoyment of learning and the sense of personal satisfaction that academic achievement can bring adds a much-needed richness to a student-centred understanding of what success in HE means.